TRANSITIONS IN DEMENTIA CARE: POST-ACUTE NEEDS AND CHALLENGES - Boltz, M (Innov Aging, 2018)
Older adults with dementia have greater nursing facility utilization, hospital and home health use, and relocation transitions per person-year than those without dementia. Hospital to nursing home/skilled nursing facility transfers are particularly stressful and associated with challenges to rehabilitation and functional recovery. There is a growing international attention to the need to customize post-acute transitional care practices to the needs of the person with cognitive impairment. A critical first step is understanding the intrinsic and extrinsic factors influencing the health, functional recovery and quality of life for persons with dementia admitted to post-acute care. This symposium will offer five presentations that address this objective. The first presentation describes the patient-level factors to consider when developing the rehabilitation plan for persons with dementia newly admitted to US skilled nursing facilities after hospitalization. The second presentation builds on the first, exploring UK nurses’ perspectives on the key components of quality care during the transition from hospital to care homes, and their role in optimizing this transition. Next, a predictive model for discharge disposition of persons with dementia post-rehabilitative care is offered. The fourth presentation describes the post-acute utilization and outcomes, by German care setting, of individuals living with dementia. Finally, the emotional expression in persons with dementia is examined as a functional measure of interventional efficacy. Our discussant, Professor Murna Downs, will synthesize the research presentation findings, offer perspective on the conceptual similarities/dissimilarities across settings and geographies, and lead a discussion of future directions for policy and practice